2006
DOI: 10.1152/japplphysiol.00800.2005
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in the mechanical properties of tail tendons in TGF-β inducible early gene-1 knockout mice

Abstract: The purpose of this study is to investigate age-dependent changes in the architecture and mechanical properties of tendon in TGF-beta inducible early gene-1 (TIEG) knockout mice. Wild-type and TIEG knockout mice, aged 1, 2, and 15 mo, were used. The mechanical properties of tail tendons isolated from these mice were determined using uniaxial tensile ramp (0.05 mm/s) and relaxation (5 mm/s) tests, with a strain of 10%. Mechanical parameters (Young's modulus from the ramp test; fast and static stresses from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 19 publications
5
32
1
1
Order By: Relevance
“…KLF10 suppresses cell proliferation, induce apoptosis, and modulate immune system [18,21,22,54]. Although KLF10 deficient mice are reported to grow and reproduce normally [55], these mice demonstrate defects in healing potential [56,57], and abnormally enhanced T cell function resulting in aggravated atherosclerosis [54]. A transcriptome profiling study using the liver of KLF10 deficient mice reveals that KLF10 has a significant role in regulating genes that are involved in lipid and carbohydrate metabolism [23].…”
Section: Discussionmentioning
confidence: 99%
“…KLF10 suppresses cell proliferation, induce apoptosis, and modulate immune system [18,21,22,54]. Although KLF10 deficient mice are reported to grow and reproduce normally [55], these mice demonstrate defects in healing potential [56,57], and abnormally enhanced T cell function resulting in aggravated atherosclerosis [54]. A transcriptome profiling study using the liver of KLF10 deficient mice reveals that KLF10 has a significant role in regulating genes that are involved in lipid and carbohydrate metabolism [23].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum failure load and the linear stiffness of the composite were measured with a custom-made microtester, 26 which was composed of a linear servo motor (MX 80 Daedal, Irwin, PA) and a load cell with the accuracy of 0.01 N (MDB-5, Transducer Techniques, Temecula, CA). The composites with BMSC from eight dogs after 7- and 14-days incubation were used.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that TIEG transcription factors in humans and mice are involved in cellular growth control and pancreatic cancer, and biochemical characterization have demonstrated that TIEGs are transcriptional repressors (Cook et al 1998(Cook et al , 1999Cook and Urrutia 2000). Moreover, recent studies on TIEG1 knock-out mice have shown that this gene is involved in flexor tendon healing, cardiac hypertrophy, and skeletal development and maintenance (Bensamoun et al 2006;Tsubone et al 2006;Rajamannan et al 2007). Further analyses will be required to demonstrate whether the proteins identified in this study could play a similar role than TIEGs in humans or mice.…”
Section: Analysis Of Cabut Orthologs In Vertebratesmentioning
confidence: 99%